Case report: severe asymptomatic hyponatremia in Prader-Willi Syndrome. Issue 1 (December 2016) - Landau, Daniel; Hirsch, Harry; Gross-Tsur, Varda
Abstract Background Prader-Willi syndrome is a complex neurogenetic, multisystem disorder. Despite the variable endocrine abnormalities and hypothalamic-pituitary axis dysfunction, hyponatremia has been reported in only a few PWS patients. In previously reported PWS individuals, hyponatremia was associated with abnormal fluid intake or during desmopressin treatment. Case presentation We describe an infant with Prader-Willi syndrome who had severe, prolonged asymptomatic hyponatremia without a history of excessive fluid intake or desmopressin treatment. We compare the findings with those of the few other reported cases and describe, for the first time, results of a hypertonic saline infusion test and studies of adrenal cortical function. Conclusion Hyponatremia should be suspected in children with Prader-Willi syndrome, especially in infants with severe failure to thrive. Further studies are needed to determine the pathophysiology of hyponatremia in this syndrome.